Decreasing graphene synthesis temperature by catalytic metal engineering and thermal processing. Issue 3 (4th January 2018) - Zheng, Li; Cheng, Xinhong; Ye, Peiyi; Shen, Lingyan; Wang, Qian; Zhang, Dongliang; Gu, Ziyue; Zhou, Wen; Wu, Dengpeng; Yu, Yuehui
Abstract : The CVD graphene growth temperature can be lowered to 700 °C by copper engineering with carbon implantation. Abstract : Chemical vapor deposition (CVD) from gaseous hydrocarbon sources has shown great promise for large-scale graphene growth, but the high growth temperature, typically 1050 °C, requires precise and expensive equipment and makes the direct deposition of graphene in electronic device manufacturing processes unfeasible due to the severe physical damage to substrates. Here we demonstrate a facile route to synthesize graphene by catalytic metal engineering and thermal processing. The engineered catalytic metal (copper) with carbon implantation could lower the synthetic temperature to 700 °C. And the resulting graphene shows few defects, uniform morphology and high carrier mobility, comparable to CVD graphene grown at 1050 °C. This technique could expand the applications of graphene in electronic and optoelectronic device manufacturing and is compatible with conventional microelectronics technology.